KARAKTERISTIK PSIKOLOGIS ATLET SEA GAMES INDONESIA DITINJAU DARI CABANG OLAHRAGA TIM - Yahya Eko Nopiyanto; Dimyati Dimyati; Fadli Dongoran (Jurnal Sporta Saintika, 2019)
This research was aimed to investigate the psychological characteristics of Indonesian SEA Games Athletes in term of team sports. The psychological characteristics consists of motivation, self-confidence, anxiety control, mental preparation, team emphasis, and concentration. This research employed the quantitative approach using survey method with a restrospective causal-comparative design also called ex post facto. The subjects of this research were selected by means of purposive sampling technique. Subjects consisted of 83 athletes from team sports. The data were collected using Psychological Skills Inventory for Sports (PSIS) questionnaire. Those data were then analyzed using SPSS 23. the psychological characteristics consisting of aspects of motivation in the very high category with mean values (35.46), confidence in the high category with mean values (26.51), anxiety control in the high category with mean values (24.18), mental preparation in the high category with mean values (21.32), the team emphasis in the high category with mean values (15.17), and concentration in the moderate category with mean values (22.30). it can be concluded that the psychological characteristics of Indonesian SEA Games Athletes in term of team sports in the high category.